Non-invasive in vivo assessment of cardiac metabolism in the healthy and diabetic human heart using hyperpolarized 13C MRI - Rider, OJ; Apps, A; Miller, JJ; Lau, JYC; Lewis, AJM; Peterzan, MA; Dodd, MS; Lau, AZ; Trumper, C; Gallagher, F; Grist, JT; Brindle, K; et al. (Ovid Technologies (Wolters Kluwer Health), 2020)
Rationale: The recent development of hyperpolarized 13C Magnetic Resonance Spectroscopy (MRS) has made it possible to measure cellular metabolism in vivo, in real time.